THE INFLUENCE OF USING TED-TALK MEDIA ON STUDENTS’ SPEAKING SKILL - Misriyana Middeleyin; Rampeng; Andi Hamzah Fansury (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This research is aim to find out whether there is a significant influence of using Technology, Entertainment, and Design) TED-Talk media on students’ speaking skill. This research uses the pre-experimental research method. The population of this research is students of the second-grade of IPA 3 of SMAN 1 Mamuju in academic year 2021/2022. The number of the sample are 20 students. The researcher collected the data by giving pre-test, treatment, post-test, and questionnaire. The data of this research is analyzed by SPSS 24 version. The researcher conludes that there was significant influence of using TED-Talk media on students’ speaking skill. It supported by the results of mean score in pre-test and post-test. The mean score in pre-test was 42.60, while in post-test was 79.00. The results of this study shows that the significance value is 0.000, which is smaller than 0.05. It shows that the the alternative hypothesis is accepted and the null hypothesis is rejected. This means that there are significant influence of using TED-Talk on students’ speaking skill.